Preparation and application of a sodium ion battery positive electrode active material and its sodium-containing single crystal precursor
The precipitation method is used to prepare a single crystal rod-like precursor of sodium-containing microns. The gradient pH reaction and the reverse equilibrium reaction of water-soluble sodium salts are solved, and the problem of poor rate performance of the positive electrode material of sodium ion battery and complex preparation method is realized. Improve performance and simplify preparation process.
Patent Information
- Application Number
- CN202211593763.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The current sodium ion battery layered oxide positive electrode materials have poor rate performance, and the preparation method has problems such as uneven distribution of sodium ions, miscellaneous phases of reaction products, lack of battery-grade sodium salts, long preparation process, and high energy consumption.
The precipitation method is used to prepare a single crystal rod-shaped precursor of sodium-containing microns. Through the two-stage gradient pH reaction assisted by activator and the third-stage reverse equilibrium reaction of water-soluble sodium salt, the formation of special crystal surfaces and rod-shaped structures is induced to achieve the Synchronous precipitation of sodium.
It improves the storage and transmission path of sodium ions, improves the capacity, magnification, circulation stability and air resistance of the material, simplifies the preparation process, and reduces energy consumption.
Smart Images

Figure CN116143613B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion secondary batteries, and in particular to the field of positive electrode active materials of sodium ion batteries. Technical Background
[0002] Affected by the tight supply of lithium resources, sodium-ion batteries have entered the public eye due to their low price and abundant and extensive reserves. Among the positive electrode materials of sodium-ion batteries, layered oxide materials have become a research direction with great development prospects due to their high specific capacity and operating voltage, as well as similar preparation processes to lithium-ion batteries.
[0003] The crystal structure of layered oxide materials is composed of repeated stacking of sodium ion layers and transition metal layers. During the charge and discharge process, sodium ions can only be embedded and extracted from the two-dimensional channels of the crystal plane family parallel to the c-axis direction, and this type of crystal plane is not easy to grow when the crystal naturally nucleates. In addition, during the electrochemical cycle, affected by the changes in the valence state of metal elements, changes in the lattice volume, and electrolyte corrosion, transition metal atoms are prone to undergo Jan-Taylor distortion and slip to the sodium ion layer, further hindering the migration and transport of sodium ions. Therefore, compared with other positive electrode materials for sodium ion batteries with three-dimensional channels, the rate performance of layered oxide materials is severely limited.
[0004] In view of the poor rate performance of layered oxide positive electrodes for sodium-ion batteries, current research on the positive electrode side is mainly focused on three aspects. The first is to nanosize the material as much as possible to shorten the transmission distance of sodium ions in the material as a means to improve the rate performance of the material, but the extremely high surface activity of the nanosized particles will aggravate the corrosion of the electrolyte on the positive electrode, resulting in a shortened cycle life. The second is to construct a fast-conducting sodium protective layer on the surface of the layered oxide material to prevent the side reactions in the electrochemical process from damaging the sodium ion transmission channel of the material, but this type of method will reduce the capacity of the positive electrode material and cannot change the essential problem of insufficient sodium ion transmission channels. The third is to reduce the crystal structure changes of the layered oxide material during the electrochemical process by doping with inactive impurities, so as to improve the safety of the sodium ion transmission channel by inhibiting the migration of transition metals, but this also cannot change the problem of insufficient sodium ion transmission channels in the layered oxide positive electrode material.
[0005] In addition, unlike conventional lithium-ion battery positive electrode materials, sodium-ion battery active materials are difficult to obtain stoichiometric sodium-containing precursors based on conventional precipitation methods, as is the case with lithium active materials, due to the good solubility of sodium salts. Therefore, for the preparation of sodium-ion positive electrode active materials, the conventional preparation ideas are mainly: (1) obtaining a transition metal precursor based on existing methods, and then calcining it with a sodium source; (2) preparing a precursor by a hydrothermal method, and then calcining it; (3) forming a precursor by sol-gel, solvent evaporation and other methods, and then calcining it. However, the above preparation methods have problems such as uneven sodium ion distribution, impurities in the reaction products, lack of battery-grade sodium salts, long preparation process, and high energy consumption. In addition, the morphology and crystal plane inheritance of the active materials prepared by the existing preparation methods of sodium-ion battery active materials are difficult to control, and the performance of the materials needs to be improved. Summary of the invention
[0006] In view of the problems in the preparation of existing sodium ion battery precursors, the first purpose of the present invention is to provide a sodium-containing micron-sized single-crystal rod-like precursor (also referred to as a precursor in the present invention), aiming to provide a micron-sized single-crystal rod-like sodium ion battery precursor material with a stoichiometric ratio.
[0007] The second purpose of the present invention is to provide a method for preparing the sodium-containing micron-sized single-crystal rod-like precursor, aiming to innovatively prepare the special sodium-containing precursor material based on a precipitation method.
[0008] The third object of the present invention is to provide a sodium ion battery positive electrode active material (also referred to as positive electrode active material in the present invention) with exposed {010} crystal planes, aiming to provide a positive electrode active material with a special physical phase, chemical structure and excellent electrochemical properties.
[0009] The fourth object of the present invention is to provide a method for preparing the sodium ion battery positive electrode active material with exposed {010} crystal planes, aiming to provide a method for preparing a new active material that inherits the phase and morphology characteristics of the precursor.
[0010] The fifth object of the present invention is to provide application of the active material in sodium ion batteries.
[0011] A sixth object of the present invention is to provide a sodium ion battery and a positive electrode thereof comprising the active material.
[0012] A sodium-containing micron-sized single-crystal rod-like precursor is a micron-sized single-crystal rod-like oxalate containing Na, Ni, Mn and M metals, and the chemical formula is: Na x Ni a Mn b M (1-a-b)C2O4: wherein, 0.5 < x ≤ 1.1; 0 ≤ a ≤ 0.8, 0 ≤ b ≤ 0.8, a and b are not both 0, and 1 - a - b > 0, and the M is at least one of K, Ca, Li, Cu, Zn, Co, Zr, Bi, Cr, Sn, La, Nb, Ti, and V.
[0013] The present invention innovatively provides a precursor material containing stoichiometric Na with the described crystal plane orientation and rod-like structure. By directly subjecting this precursor material to oxidative calcination treatment, an active material inheriting the special crystal plane orientation and rod-like morphology can be obtained, which can effectively improve the storage and transmission pathways of sodium ions, improve the strain of the crystal structure in the cycling stage, and further improve its capacity, rate performance, cycling stability, and air stability.
[0014] Preferably, x is 0.6 to 0.8; a is 0.13 to 0.6; b is 0.4 to 0.75; more preferably, x is 0.6 to 0.7; a is 0.2 to 0.4; b is 0.5 to 0.6.
[0015] Preferably, 1 - a - b is 0.01 to 0.1; more preferably 0.04 to 0.08.
[0016] Preferably, the length of the rod-like precursor is 3 to 8 μm, and the width is 0.5 to 2 μm. More preferably, the length of the rod-like precursor is 5 to 8 μm, and the width and height are 0.8 to 1.5 μm.
[0017] The present invention also provides a method for preparing the sodium-containing micron-sized single-crystal-like rod-like precursor. An aqueous solution dissolving a divalent Mn source, a divalent nickel source, an M source, an oxalic acid source, and an activator is first subjected to a first-stage reaction at a pH a , and then the pH of the system is gradually increased to pH b by using a sodium-containing alkaline substance for a second-stage reaction; then a water-soluble sodium salt is added for a third-stage reaction to obtain the sodium-containing micron-sized single-crystal-like rod-like precursor;
[0018] wherein, the activator is a C1 - C6 unit or polyol;
[0019] In the first-stage reaction system, the volume content of the activator is 20 to 50%;
[0020] pH a is 1.0 - 2.5; pH b is 4 - 7.5.
[0021] The present invention proposes for the first time in the industry a method of obtaining a precursor containing stoichiometric sodium based on a precipitation method. However, research has found that, unlike the conventional precipitation method for lithium precipitation, the solubility of sodium salts is generally large and difficult to be precipitated into the precursor. Not only that, when preparing a stoichiometric sodium precursor by a precipitation method, it is also difficult to take into account the precipitation of sodium and the joint control of the precursor morphology, phase and crystal plane orientation. In view of the technical problems faced by the preparation of the precursor of the present invention, the present invention has innovatively proposed, after research, that the reaction under the second stage gradient pH assisted by the activator is further coordinated with the control of the third stage reverse equilibrium reaction of the water-soluble sodium salt, so that unexpected synergy can be achieved, and the special crystal plane and rod-like structure can be unexpectedly induced. Not only that, it can also promote the synchronous precipitation of sodium, and a precursor with a special orientation and rod-like morphology of stoichiometric sodium can be prepared. The precursor can be directly subjected to oxidative roasting treatment to obtain an active material that inherits its special crystal plane, rod-like morphology and takes into account excellent electrochemical properties and air stability.
[0022] In the present invention, the first and second stage reactions assisted by the activator and under pH control are further coordinated with the chemical reverse equilibrium mechanism of the water-soluble sodium salt, which can unexpectedly achieve synergy and induce the rod-shaped micron-sized large single crystal structure. In addition, it is also beneficial to the concomitant precipitation of sodium and to obtain the special precursor.
[0023] In the present invention, the divalent Mn source, the divalent nickel source and the M source can be dissolved in water in advance to obtain solution A, the oxalic acid source can be dissolved in water to obtain solution B, the activator can be diluted with water to obtain solution C, and then solutions A to C can be mixed to carry out the first stage reaction.
[0024] In the present invention, the divalent Mn source, divalent nickel source, and M source are water-soluble salts of the respective metals, preferably at least one of acetate, sulfate, nitrate, and hydrochloride of the respective metals;
[0025] Preferably, in the first stage reaction system, the total metal concentration of divalent Mn, divalent nickel, and M is 0.5-1.1 M, preferably, the molar ratio is 0.67-1.05 M;
[0026] Preferably, the oxalic acid source is at least one of oxalic acid, ammonium oxalate and sodium oxalate.
[0027] Preferably, the oxalic acid source is 1 to 3 times the theoretical molar amount for completely precipitating the stoichiometric divalent Mn, divalent nickel, M, and Na in the precursor.
[0028] Preferably, the activator is a C1-C3 unit or a C2-C4 dihydric or trihydric alcohol.
[0029] In the present invention, the first stage reaction induced by the activator, the second stage reaction and the two-stage gradient pH are jointly controlled to facilitate the target orientation and the nucleation of the rod-shaped structure crystals and the accompanying precipitation of sodium. a , pH b As well as the gradient enhancement mechanism, it helps to further synergistically improve the target orientation, the formation of rod-like morphology, and facilitate the concomitant precipitation of sodium, which in turn facilitates the preparation of active materials with high electrochemical performance and air stability.
[0030] Preferably, in the first stage reaction system, the volume content of the activator is 30-40%.
[0031] Preferably, pH a It is 1.5 to 2.0, and more preferably 1.7 to 1.9.
[0032] Preferably, the first stage reaction time is 0.5 to 3.0 h.
[0033] Preferably, pH a Raise to pH b The gradient is 0.1-0.6 / h, and considering the treatment efficiency and effect, it is more preferably 0.4-0.6 / h. In the present invention, the gradient heating mechanism can further facilitate the induction of the crystal plane and rod-like morphology, and facilitate the accompanying precipitation of sodium.
[0034] Preferably, pH b It is 5.5 to 7.0, and more preferably 6 to 6.8.
[0035] Preferably, the second reaction period is 8 to 12 hours.
[0036] In the present invention, after the second stage reaction, water-soluble sodium salt is added to the system to carry out the third stage reaction, inducing the reaction equilibrium to move, thereby promoting the formation of the crystal plane, phase and sodium stoichiometric precursor.
[0037] Preferably, the water-soluble sodium salt is a high-solubility sodium salt, including at least one of sodium acetate, sodium sulfate, sodium chloride, sodium carbonate, sodium nitrate, sodium citrate, sodium ascorbate, and sodium gluconate.
[0038] Preferably, the water-soluble sodium salt is sodium acetate.
[0039] In the present invention, the temperature of the first to third reaction stages can be room temperature, for example, 5 to 45°C.
[0040] In the present invention, in the prepared precursor, each element meets the stoichiometric ratio requirement, and in addition, the sodium therein is allowed to exist in excess of 0 to 15%.
[0041] The preferred preparation method steps of the precursor of the present invention include:
[0042] (1) Add deionized water, nickel acetate, manganese acetate, and M metal acetate into container 1 to prepare an acetate mixed solution; add deionized water and oxalic acid into container 2 to prepare an oxalic acid solution; add an active agent or an active agent solution prepared by the active agent and water into container 3. Add the three solutions into the same container and keep the mixed solution stirring continuously, and carry out the first-stage reaction at pH a value;
[0043] The M metal acetate includes one or more of potassium acetate, calcium acetate, lithium acetate, copper acetate, zinc acetate, cobalt acetate, zirconium acetate, bismuth acetate, cadmium acetate, tin acetate, lanthanum acetate, niobium acetate, titanium acetate, and vanadium acetate. The concentration of M ions is 0.1-2 mol / L, preferably 0.5-1 mol / L.
[0044] In the starting solution of the first-stage reaction, the concentration of oxalic acid is 1-2 mol / L; the active agent is one or more of ethylene glycol and ethanol. The volume concentration of the active agent is 20-50%; the stirring speed is 600-1000 r / min; pH a is 1.0-2.5.
[0045] (2) After the first-stage reaction, reduce the stirring speed and adjust the pH value of the solution to pH b value by adding NaOH solution to carry out the second-stage reaction, and then add sodium acetate solution to obtain a sodium-containing precursor that meets the stoichiometry. The stirring speed is 200-400 r / min; use sodium hydroxide solution to adjust the mixed solution to pH b value at a speed of 0.5 / h, and it is 4-7.5.
[0046] Adding sodium acetate promotes the crystallization and precipitation of sodium oxalate and adjusts the molar ratio of the total amount of sodium in the precursor to the total amount of transition metals to be 0.5-1.1, preferably the molar ratio is 0.67-1.05.
[0047] The present invention also provides a sodium-ion battery cathode active material exposing the {010} crystal plane, which is a Na x Ni a Mn b M 1-a-b O2 layered material with an exposed {010} crystal plane and a rod-like structure, where 0.5 < x ≦ 1.1, 0 ≦ a ≦ 0.8, 0 ≦ b ≦ 0.8, a and b are not both 0, and M is at least one of K, Ca, Li, Cu, Zn, Co, Zr, Bi, Cr, Sn, La, Nb, Ti, and V.
[0048] The invention provides an active material with a special crystal plane orientation and a rod-like structure, wherein the material has an excellent sodium transport network, can buffer crystal stress, and has excellent capacity, cycle stability and air resistance stability.
[0049] In the active material, x is 0.6 to 0.8; a is 0.13 to 0.6; b is 0.4 to 0.75; more preferably, x is 0.6 to 0.7; a is 0.2 to 0.4; b is 0.5 to 0.6.
[0050] Preferably, 1-ab is 0.01 to 0.1; more preferably, it is 0.04 to 0.08.
[0051] The present invention also provides a method for preparing the sodium ion battery positive electrode active material with exposed {010} crystal planes, wherein the sodium-containing micron-sized single-crystal rod-shaped precursor is prepared by the method, and then directly calcined in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode active material with exposed {010} crystal planes.
[0052] In the present invention, thanks to the innovation of the special crystal plane, rod-like structure and the precipitation method sodium precursor that meets the stoichiometric ratio, the material inheriting the special crystal plane and morphology of the precursor and having an active material with excellent crystal purity can be obtained without direct calcination under sodium. The material prepared by the present invention has excellent electrochemical properties.
[0053] Preferably, the oxygen-containing atmosphere is a mixture of air and oxygen-protective gas;
[0054] Preferably, the roasting process includes a first heat preservation process and a second heat preservation process, wherein the temperature T1 of the first heat preservation process is preferably 300 to 600° C., and more preferably 400 to 550° C.;
[0055] Preferably, the first insulation time is 2 to 10 hours, preferably 5 to 8 hours;
[0056] Preferably, the temperature T2 of the second insulation process is preferably 700-950°C, more preferably 800-950°C, and even more preferably 850-900°C;
[0057] Preferably, the second insulation time is 12-25 hours, preferably 15 to 20 hours.
[0058] During the calcination stage, the heating rate is 1 to 10°C / min.
[0059] The present invention also provides an application of the sodium ion battery positive electrode active material with exposed {010} crystal planes, which is used as a positive electrode active material for preparing a sodium ion battery;
[0060] Preferably, it is used as a positive electrode active material to prepare a positive electrode of a sodium ion battery.
[0061] The present invention can prepare the active material of the present invention to form a sodium ion battery and a positive electrode thereof based on existing methods.
[0062] For example, based on conventional industry principles and methods, the active material is compounded with a conductive agent and a binder to form a positive electrode material, which is further slurried and coated on a current collector to form a positive electrode. The positive electrode, separator and negative electrode are then assembled to form a battery cell, and the battery cells are assembled to form a sodium ion battery.
[0063] The present invention also provides a sodium ion battery positive electrode material, comprising the sodium ion battery positive electrode active material with exposed {010} crystal planes.
[0064] The positive electrode material of the present invention, in addition to the active material, is also allowed to contain at least one of a conductive agent and a binder. Preferably, the weight content of the active material is 70%-95%, and the content of the binder and the conductive agent may preferably be less than or equal to 15wt%.
[0065] The present invention also provides a sodium ion battery positive electrode, which comprises a current collector and a positive electrode material composited on the current collector.
[0066] The present invention also provides a sodium ion battery, comprising the sodium ion battery positive electrode active material with exposed {010} crystal planes as described in the present invention.
[0067] In the present invention, the sodium ion battery, except for the active material described in the present invention, other materials and components can be conventional.
[0068] Beneficial Effects
[0069] 1. The present invention innovatively provides a precursor material containing a stoichiometric amount of Na and having the rod-shaped micron-sized large single crystal structure. The precursor material is directly subjected to oxidation roasting treatment to obtain an active material inheriting the special crystal plane orientation and rod-shaped morphology, which can effectively improve the storage and transmission pathways of sodium ions, improve the strain of the crystal structure in the cycle stage, and further improve its capacity, rate, cycle stability and air resistance stability.
[0070] 2. In view of the technical problems faced by the preparation of the precursor of the present invention, the present invention has innovatively proposed, after research, that the reaction under the second-stage gradient pH assisted by the activator is further coordinated with the control of the third-stage reverse equilibrium reaction of the water-soluble sodium salt, so that unexpected synergy can be achieved, and the special crystal plane and rod-like structure can be unexpectedly induced. Not only that, it can also promote the synchronous precipitation of sodium, and a precursor with a special orientation and rod-like morphology of stoichiometric sodium can be prepared. The precursor can be directly subjected to oxidative roasting treatment to obtain an active material that inherits its special crystal plane, rod-like morphology and takes into account excellent electrochemical properties and air resistance stability.
[0071] 3. The present invention provides an active material with a special crystal plane orientation and a rod-like structure, which has an excellent sodium transport network and can buffer crystal stress, and has excellent capacity, cycle stability and air resistance stability.
[0072] 4. In the present invention, thanks to the special crystal face, rod-like structure and the innovation of the sodium precursor of the precipitation method that meets the stoichiometric ratio, the material inheriting the special crystal face and morphology of the precursor and having an active material with excellent crystal purity can be obtained without direct calcination under sodium. The material prepared by the present invention has excellent electrochemical properties and air resistance stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is a scanning electron microscope image of the oxalate precursor of the sodium ion battery layered oxide positive electrode material with the {010} crystal plane exposed in Example 1 of the present invention;
[0074] Figure 2 This is a scanning electron microscope image of the sodium ion battery layered oxide positive electrode material with the {010} crystal plane exposed in Example 1 of the present invention;
[0075] Figure 3 This is a transmission electron microscope image of the sodium ion battery layered oxide positive electrode material with the {010} crystal plane exposed in Example 1 of the present invention;
[0076] Figure 4 This is a scanning electron microscope image of the oxalate precursor of the sodium ion battery layered oxide positive electrode material with the {010} crystal plane exposed in Group A of Example 2 of the present invention;
[0077] Figure 5 The XRD diffraction pattern of the sodium ion battery layered oxide positive electrode material with exposed {010} crystal plane in Example 1 of the present invention is compared with that in Comparative Example 1. DETAILED DESCRIPTION
[0078] The raw materials used in this example are all analytical grade raw materials.
[0079] Example 1
[0080] (1) manganese acetate, nickel acetate, zinc acetate, and copper acetate are taken according to the molar ratio of transition metal elements of 0.60:0.32:0.04:0.04, and dissolved in a deionized water solution so that the concentration of transition metal atoms (Mn-Ni-Zn-Cu in this case) is 0.5 mol / L; oxalic acid is dissolved in deionized water so that the concentration of oxalic acid is 1 mol / L;
[0081] (2) The transition metal solution, oxalic acid solution and ethylene glycol were simultaneously dripped into the same container through a peristaltic pump, and the mixed solution in the container was kept stirred at a speed of 600 r / min to carry out the first stage of reaction (time of 2 h). The dripping rate of the above three solutions was controlled so that the volume proportion of ethylene glycol in the mixed solution was 35%, and the pH value of the mixed solution was pH a is 1.8; the molar ratio of oxalic acid to manganese, nickel, zinc and copper is 3:1.
[0082] (3) After the solution is mixed, adjust the rotation speed of the mixed solution to 200 r / min, and adjust the pH value of the mixed solution to pH 5 at a rate of 0.5 / h using a 1 mol / L sodium hydroxide solution. b The pH value was 6.5, and the second treatment was carried out (the total time including the time of gradient pH increase was 11 h), and then continuous stirring was maintained until the precursor precipitate crystals grew to more than 5 μm;
[0083] (4) Sodium acetate is then added to promote the reaction and the molar ratio of sodium to transition metal in the precursor is controlled to be 0.70:1. The resulting slurry is dried to obtain a sodium-containing precursor with preferential crystal growth (SEM). Figure 1 ).
[0084] (5) The precursor prepared by room temperature precipitation crystallization was calcined in an oxygen atmosphere in two stages, with the first stage temperature T1 being 500°C and kept at this temperature for 6 h (t1), and then the temperature was raised to the second stage temperature for keeping at this temperature, wherein the second stage temperature was 900°C and kept at this temperature for 20 h (t2), and the heating rate was 3°C / min. After the calcination process was completed, the target sodium ion battery layered oxide positive electrode material with exposed {010} crystal plane was obtained (SEM image see Figure 2 , TEM Figure 3 , XRD see Figure 5 ).
[0085] Example 2
[0086] Compared with Example 1, the only difference between Group A and Example 1 is that zinc acetate in step (1) is replaced by an equimolar amount of copper acetate, and the molar ratio of transition metal elements is replaced by Mn:Ni:Cu molar ratio of 0.60:0.32:0.08, and other steps and parameters remain unchanged; SEM image is shown in Figure 4 ;
[0087] The only difference between Group B and Example 1 is that the molar ratio of transition metal elements of manganese acetate, nickel acetate, zinc acetate and copper acetate in step (1) is replaced with 0.75:0.17:0.04:0.04, and the other steps and parameters remain unchanged.
[0088] Example 3
[0089] The only difference between Group A and Example 1 is that ethylene glycol in step (2) is replaced by ethanol, and the other steps and parameters remain unchanged;
[0090] The only difference between Group B and Example 1 is that the volume proportion of ethylene glycol in the mixed solution in step (2) is replaced by 25%, and the other steps and parameters remain unchanged.
[0091] Example 4
[0092] The difference between Group A and Example 1 is that the pH in step (2) a Replace with 1.0, and keep other steps and parameters unchanged;
[0093] The only difference between Group B and Example 1 is that the pH in step (3) b Replace it with 7.5, and keep other steps and parameters unchanged.
[0094] Example 5
[0095] The only difference between Group A and Example 1 is that T1 in step (5) is replaced by 350°C, and the other steps and parameters remain unchanged;
[0096] The only difference between Group B and Example 1 is that T2 in step (5) is replaced by 800° C., and the other steps and parameters remain unchanged.
[0097] Comparative Example 1
[0098] Compared with Example 1, the only difference is that in step (1), zinc acetate and copper acetate are missing, and the molar ratio of Mn / Ni is 0.6:0.4, and other steps and parameters remain unchanged.
[0099] Comparative Example 2
[0100] Compared with Example 1, the activator ethylene glycol was not added in step (2), and the other steps and parameters remained unchanged; no similar large single crystal precursor was obtained.
[0101] Comparative Example 3
[0102] Compared with Example 1, the pH in step (2) a Change to 3.5, and keep other steps and parameters unchanged.
[0103] Comparative Example 4
[0104] Compared with Example 1, step (3) pH a Raise to pH within 10 minutes b , other steps and parameters remain unchanged.
[0105] Comparative Example 5
[0106] Compared with Example 1, step (3) pH b Change to 3.5, and keep other steps and parameters unchanged.
[0107] Comparative Example 6
[0108] Compared with Example 1, an equal amount of sodium acetate in step (4) is added at once at the beginning of the reaction in step (2), and step 5 is directly performed after step 3, while other steps and parameters remain unchanged.
[0109] Comparative Example 7
[0110] Compared with Example 1, the only difference is that step 4 is not performed, and the product of step 3 is directly subjected to sodium roasting. For example, the product of step 3 and sodium acetate are mixed according to the ratio of Example 1, and then the treatment of step 5 is performed. Other operations and parameters are the same as those of Example 1.
[0111] Comparative Example 8
[0112] Compared with Example 1, the only difference is that stoichiometric amounts of manganese oxalate, nickel oxalate, zinc oxalate, copper oxalate and sodium acetate are directly mixed in liquid phase, then evaporated to form a precursor, and then the calcination treatment of step 5 is performed.
[0113] The main test steps are:
[0114] (1) The layered oxide positive electrode material obtained in the above-mentioned embodiments and comparative examples is used as the positive electrode active material, and the active material is mixed with conductive carbon (acetylene black) and a binder (PVDF) in a mass ratio of 8:1:1. A positive electrode is prepared using aluminum foil as a current collector. At the same time, glass fiber is used as a separator, a homemade metal sodium sheet is used as a negative electrode, and 1M NaClO4 dissolved in PC+5% FEC solution is used as an electrolyte to assemble a 2032-type button battery.
[0115] (2) The assembled battery was placed at a constant temperature of 25°C for 10 h, and then subjected to an electrochemical test procedure of charging first and then discharging.
[0116] (3) The test voltage range is set to 2.0-4.3V, the first ten cycles are a low rate test of 0.1C, and the next ten cycles are a high rate test of 5C. The theoretical capacity is 170mAh / g.
[0117] The temperature of the storage process under air is room temperature, and the air humidity is 10-35RH%.
[0118] The test results are shown in Table 1:
[0119] Table 1 Electrochemical performance test results
[0120]
[0121] Note: Newly made materials refer to fresh materials after T2 stage roasting and furnace cooling, and the time they are exposed to air is less than or equal to 12h.
[0122] As can be seen from Table 1, by directly calcining the precursor with a special stoichiometric structure constructed by the first to third reactions of the present invention, better electrochemical performance and air resistance stability can be obtained.
Claims
1. A method for preparing a sodium-containing micron-sized single-crystal rod-like precursor, characterized in that: The sodium-containing micron-scale single-crystal rod-like precursor is a micron-scale single-crystal rod-like oxalate containing Na, Ni, Mn, and metal M, and its chemical formula is: Na x Ni a Mn b M (1-a-b) C2O4: where 0.5 < x ≦ 1.1; 0 < a ≦ 0.8, 0 < b ≦ 0.8, a and b are not both 0, 1 - a - b > 0, and the said M is Cu, or M is Cu and Zn; The steps of preparing the sodium-containing micron-sized single crystal rod-like precursor include: preliminarily dissolving a divalent Mn source, a divalent nickel source, an M source, an oxalic acid source, and an activator in an aqueous solution at a pH of a The first stage of the reaction was carried out under the condition of sodium-containing alkaline substances, and then the pH gradient of the system was raised to pH b , and carry out a second stage reaction; then add a water-soluble sodium salt and carry out a third stage reaction to obtain the sodium-containing micron-sized single-crystal rod-like precursor; Wherein, the activator is a C1-C6 unit or polyol; In the first stage reaction system, the volume content of the activator is 20-50%; pH a 1.0-2.5; pH b 4-7.5; The sodium-containing alkaline substance is sodium hydroxide; The water-soluble sodium salt is at least one of sodium acetate, sodium citrate, sodium ascorbate and sodium gluconate; The activator is a C1-C3 monoalcohol or a C2-C4 dihydric or trihydric alcohol; pH a Raise to pH b The gradient is 0.1~0.6 / h.
2. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: x is 0.6~0.8; a is 0.13~0.6; b is 0.4~0.
75.
3. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: x is 0.6~0.7; a is 0.2~0.4; b is 0.5~0.
6.
4. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: 1-ab is 0.01~0.
1.
5. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: 1-ab is 0.04~0.
08.
6. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: The rod-shaped precursor has a length of 3 to 8 μm, and a width and height of 0.5 to 2 μm.
7. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: The divalent Mn source, divalent nickel source and M source are water-soluble salts of their respective metals.
8. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 7, characterized in that: The divalent Mn source, divalent nickel source and M source are at least one of acetate, sulfate, nitrate and hydrochloride of the respective metals.
9. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: In the first stage reaction system, the total metal concentration of divalent Mn, divalent nickel and M is 0.5-1.1M, and the molar ratio is 0.67-1.05M.
10. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: The oxalic acid source is at least one of oxalic acid, ammonium oxalate and sodium oxalate.
11. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: The oxalic acid source is 1 to 3 times the theoretical molar amount for completely precipitating the stoichiometric divalent Mn, divalent nickel, M and Na in the precursor.
12. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: In the first stage reaction system, the volume content of the activator is 20-50%.
13. The method for preparing a sodium-containing micron-sized single-crystal rod-like precursor according to claim 1, characterized in that: The water-soluble sodium salt is sodium acetate.
14. A method for preparing a positive electrode active material for a sodium ion battery exposing a {010} crystal plane, characterized in that: The sodium-containing micron-sized single-crystal rod-shaped precursor is prepared by the preparation method described in any one of claims 1 to 13, and then calcined in an oxygen-containing atmosphere to obtain the sodium ion battery positive electrode active material with exposed {010} crystal planes.
15. The method for preparing a positive electrode active material for a sodium ion battery with exposed {010} crystal planes according to claim 14, characterized in that: The oxygen-containing atmosphere is a mixture of air and oxygen-protective gas.
16. The method for preparing a positive electrode active material for a sodium ion battery with exposed {010} crystal planes according to claim 14, characterized in that: The roasting process includes a first heat preservation process and a second heat preservation process, wherein the temperature T1 of the first heat preservation process is 300-600°C.
17. The method for preparing a positive electrode active material for a sodium ion battery with exposed {010} crystal planes according to claim 14, characterized in that: The first insulation time is 2 to 10 hours.
18. The method for preparing a positive electrode active material for a sodium ion battery with exposed {010} crystal planes according to claim 14, characterized in that: The temperature T2 of the second insulation process is 700-950℃.
19. The method for preparing a positive electrode active material for a sodium ion battery with exposed {010} crystal planes according to claim 14, characterized in that: The second insulation time is 12-20h.